Obese Patients Undergoing Ileal Pouch–Anal Anastomosis: Short-and Long-term Surgical Outcomes. Issue 12 (December 2017) - McKenna, Nicholas P.; Mathis, Kellie L.; Khasawneh, Mohammad A.; Dozois, Eric J.; Larson, David W.; Pemberton, John H.; Lightner, Amy L.
Abstract : Background: Ileal pouch–anal anastomosis (IPAA) is the preferred surgical treatment for patients with chronic ulcerative colitis. Little is known about the impact of obesity on operative characteristics, short-term postoperative complications and long-term functional outcomes after IPAA. Methods: A retrospective review of all patients undergoing IPAA for chronic ulcerative colitis at a single tertiary referral center between January 2002 and August 2013 was performed. Thirty-day postoperative complications and long-term functional outcomes were analyzed according to body mass index. Results: Nine hundred nine IPAAs (154 obese [body mass index ≥ 30] and 755 not obese [body mass index < 30]) were performed during the study period. For 2-stage IPAA, obese patients were less likely to undergo laparoscopic IPAA ( P < 0.0001), had greater estimated blood loss ( P = 0.005), and longer operative times ( P = 0.02). For 3-stage IPAA, obese patients were less likely to undergo a laparoscopic procedure ( P = 0.03), had greater estimated blood loss ( P < 0.0001), and longer operative times ( P = 0.0002). Postoperatively, obese patients had a longer length of stay after a 2-stage procedure ( P = 0.009), an increased rate of superficial surgical site infections ( P = 0.003), and an increased rate of urinary tract infections ( P = 0.03). Of the 61% (n = 546) of patients with IPAA with long-term (median 5.0 years) follow-up, there were no significant differences in functional outcomes including incontinence, frequency of bowel movements, pad usage, and pouchitis between the groups. Conclusions: Obesity impacts intraoperative complexity and 30-day postoperative outcomes. Long-term functional outcomes are not affected. These findings underscore the need to counsel patients on preoperative weight loss before undergoing elective IPAA. Abstract : Article first published online 23 August 2017.